The role of family economic education in Islamic perspective / Yani Nuraeni and Dini Nurdiani - Nuraeni, Yani; Nurdiani, Dini (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study discusses the role of economic education in the family from an Islamic perspective. This research is library research or library research, which relies on sources on library materials. The results of this study are the role of economic education related to aspects of education in the family. The family must apply habits such as saving, being thrifty, and being selective in purchasing goods and services. This habituation will form a mindset that is manifested in economic education literacy. The role of economic education is related to religious aspects in the family, namely the father or mother introduces Islamic economics education to their family members, which is close to religious nuances such as teaching that Islam requires that every human activity is not only worldly (material) value, but should also have spiritual value.